Implementasi Diplomasi Budaya Indonesia melalui Kerja Sama Pendidikan terhadap Korea Selatan (2021-2023) - Tisnakusumahnita, Azizah; Putri, Sylvia Octa (Universitas Komputer Indonesia, 2024)
This article aims to analyse the implementation of Indonesia's cultural diplomacy through educational cooperation towards South Korea in 2021-2023. This research outlines Indonesia's cultural diplomacy efforts through educational cooperation towards South Korea, such as cultural activities in overseas educational institutions, Indonesian language courses/classes, scholarships, and student exchanges. In addition, it also describes the constraints and opportunities, as well as the results of Indonesia's cultural diplomacy through educational cooperation towards South Korea. The researcher used a qualitative approach, with data collected from various sources, including literature studies and interviews. The results of this study show that there is an increase in the interest of students and the South Korean community in knowing Indonesian culture as seen from the achievements of the programmes that have been implemented. However, there are still obstacles, especially in terms of funding and limited human resources and promotion. Therefore, to maximise this effort, collaboration from various parties is needed. This article is expected to be a reference for further research and comparison material for students who want to develop research in the same field. Keywords — Cultural Diplomacy, Education Cooperation, Indonesia, South Korea